Design Strategies of High‐Performance Positive Materials for Nonaqueous Rechargeable Aluminum Batteries: From Crystal Control to Battery Configuration. Issue 27 (27th May 2022) - Tu, Jiguo; Wang, Wei; Lei, Haiping; Wang, Mingyong; Chang, Cheng; Jiao, Shuqiang
Abstract: Rechargeable aluminum batteries (RABs) have been paid considerable attention in the field of electrochemical energy storage batteries due to their advantages of low cost, good safety, high capacity, long cycle life, and good wide‐temperature performance. Unlike traditional single‐ion rocking chair batteries, more than two kinds of active ions are electrochemically participated in the reaction processes on the positive and negative electrodes for nonaqueous RABs, so the reaction kinetics and battery electrochemistries need to be given more comprehensive assessments. In addition, although nonaqueous RABs have made significant breakthroughs in recent years, they are still facing great challenges in insufficient reaction kinetics, low energy density, and serious capacity attenuation. Here, the research progresses of positive materials are comprehensively summarized, including carbonaceous materials, oxides, elemental S/Se/Te and chalcogenides, as well as organic materials. Later, different modification strategies are discussed to improve the reaction kinetics and battery performance, including crystal structure control, morphology and architecture regulation, as well as flexible design. Finally, in view of the current research challenges faced by nonaqueous RABs, the future development trend is proposed. More importantly, it is expected to gain key insights into the development of high‐performance positive materials for nonaqueous RABs to meet practical energy storage requirements. Abstract : Positive materials for rechargeable aluminum batteries have made significant breakthroughs in recent years. For dealing with great challenges in insufficient reaction kinetics, the modification strategies of high‐performance positive materials, including crystal structure control, morphology and architecture regulation, as well as flexible design, are regarded as the most effective methods to promote battery development toward better dynamic processes and electrochemical performance.